Pengaruh Kualitas Layanan, Produk Indihome Dan Promosi Terhadap Pelanggan PT. Telkom indonesia (Persero) tbk di Kota Palopo - Hijrah Haji Tampa (Jurnal Online Manajemen ELPEI, 2022)
This study aims to analyze the influence of service quality, products and promotions on customer satisfaction at PT. Telkom Indonesia (Persero) Tbk Palopo city. This research was conducted at PT. Telkom Indonesia (Persero) Tbk Palopo city. with a population and a sample of all customers totaling 50 people. Data was collected by distributing questionnaires and documentation. Data were analyzed through Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, and the Coefficient of Determination (R2), using the SPSS application. The results showed that service and product quality had a positive and significant effect on customer satisfaction, while promotions had a positive and insignificant effect on customer satisfaction. The dominant product variable influences customer satisfaction at PT. Telkom Indonesia (Persero) Tbk Palopo city.